DAMPAK IMPLEMENTASI KEBIJAKAN THE GREAT FIREWALL OLEH PEMERINTAH CHINA TERHADAP AKTIVITAS GOOGLE INC DI CHINA (2006 – 2012) - MUhammad Yusrizal; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This reasearch focused on the impact of the Great Firewall Policy Implementation By Chinese Government Activity Against Google Inc. in China. The Chinese government has imposed strict censorship on google is a search engine that provides information and news in general and can be freely accessed by Internet users, however the information must first be carried out through a filtering process that the Chinese government, if the keyword is searched contains views negative towards the government instantly sought information that would be blocked by the Chinese government and disappear from google search.This reasearch used qualitative data sourced from books, journals and websites that will explain the measures the Chinese government to suppress the development of google inc doing business in China. This study uses the theory of decision-making and Richard Snyder, H. W. Buck, and Burton Sapin and using Nation state level analysisThe results of this study found that the Chinese government has managed to make google did not develop in Chinese even google has resigned from China in 2010 because it is always under pressure from the government. Pullback google has a positive impact on the development of a local search engine company Baidu can utilize mainly the conflict between the Chinese government with Google, Baidu has attracted widespread sympathy for the Chinese people to use local products. At this time Baidu has dominated more than 70% of Internet users in ChinaKeyword: Policy, Decision-making, Filtering Process, Google and Baidu